Slc25a21 in cisplatin-induced acute kidney injury: a new target for renal tubular epithelial protection by regulating mitochondrial metabolic homeostasis - Xin Su; Mi Bai; Yaqiong Shang; Yang Du; Shuang Xu; Xiuli Lin; Yunzhi Xiao; Yue Zhang; Huimei Chen; Aihua Zhang (Cell Death and Disease)
Abstract Acute kidney injury (AKI) is a significant global health issue, which is often caused by cisplatin therapy and characterized by mitochondrial dysfunction. Restoring mitochondrial homeostasis in tubular cells could exert therapeutic effects. Here, we investigated Slc25a21, a mitochondrial carrier, as a potential target for AKI intervention. Renal Slc25a21 expression is negatively associated with kidney function in both AKI patients and cisplatin-induced murine models. Sustaining renal expression of Slc25a21 slowed down AKI progression by reducing cellular apoptosis, necroptosis, and the inflammatory response, likely through its regulation of 2-oxoadipate conversion. Slc25a21 is highly expressed in proximal tubular epithelial cells, and its down-regulation contributes to compromised mitochondrial biogenesis and integrity, as well as impaired oxidative phosphorylation. Mechanistically, reduced Slc25a21 in AKI disrupts mitochondrial 2-oxoadipate transport, affecting related metabolites influx and the tricarboxylic acid cycle. These findings demonstrate a previously unappreciated metabolic function of Slc25a21 in tubular cells, and suggest that targeting mitochondrial metabolic homeostasis by sustaining Slc25a21 expression could be a potential novel therapeutic strategy for AKI.